Emerging role of antidiabetic drugs in cardiorenal protection - Fu, Wen-Jia; Huo, Jin-Ling; Mao, Zi-Hui; Pan, Shao-Kang; Liu, Dong-Wei; Liu, Zhang-Suo; Wu, Peng; Gao, Zhong-Xiuzi (Frontiers in Pharmacology, 2024)
The global prevalence of diabetes mellitus (DM) has led to widespread multisystem damage, especially in cardiovascular and renal functions, heightening morbidity and mortality. Emerging antidiabetic drugs sodium-glucose cotransporter 2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP-1RAs), and dipeptidyl peptidase-4 inhibitors (DPP-4i) have demonstrated efficacy in preserving cardiac and renal function, both in type 2 diabetic and non-diabetic individuals. To understand the exact impact of these drugs on cardiorenal protection and underlying mechanisms, we conducted a comprehensive review of recent large-scale clinical trials and basic research focusing on SGLT2i, GLP-1RAs, and DPP-4i. Accumulating evidence highlights the diverse mechanisms including glucose-dependent and independent pathways, and revealing their potential cardiorenal protection in diabetic and nondiabetic cardiorenal disease. This review provides critical insights into the cardiorenal protective effects of SGLT2i, GLP-1RAs, and DPP-4i and underscores the importance of these medications in mitigating the progression of cardiovascular and renal complications, and their broader clinical implications beyond glycemic management.